Analisis Kerusakan Pekerasan Lentur Jalan pada Ruas Jalan Raya Babat Kabupaten Lamongan dengan Metode Bina Marga - Farokhman, Moh Fani; Tjendani, Hanie Teki (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This research aims to analyze the types of pavement damage, calculate the road damage index, and determine appropriate maintenance actions using the Bina Marga method. The study was conducted over a 5.6 km stretch of road, divided into 23 segments. Based on visual survey data and Average Daily Traffic (ADT), the damage index for each segment was calculated. The analysis results show that the road segments experienced varying levels of damage, with the lowest condition score recorded at 4 and the highest at 9, indicating road conditions ranging from moderate to severe. Specifically, 39.13% of the segments (9 out of 23) were categorized as having minor damage, 47.83% (11 segments) as moderate damage, and 13.04% (3 segments) as severely damaged. The recommended maintenance strategies include routine and periodic maintenance, with priority given to segments scoring below 6. The findings are expected to support local authorities in planning effective and timely road maintenance, thus enhancing road safety and user comfort.